Legal issues of service and combat activities security forces in social emergency situations - Мацюк, В. В. (Problems of legality, 2015)
The analysis of regulatory support service and combat activity of the forces of law and order in social emergency situations is realised. The basic problems are determined for of legal regulation of service and combat activity of the forces of law and order in social emergency situations. The main ground is proved for need to introduce in the south-eastern regions of Ukraine emergency legal and administrative regimes.